The European Union and peace in Sub-Saharan Africa - (:unkn) unknown (My University, 2012)
Sub-Saharan Africa is faced with crises and conflicts that also pose a threat to the security of Europe, the United States and the world at large.Africa seeks to ensure its own security and calls on the aid of foreign partners including Europe. But questions arise concerning the strengths and realities of that partnership and the prospects for peace it offers.The European Union is indeed a partner whose effectiveness - guaranteed by the comprehensive approach embodied in its multifaceted ACP/EEC-EU and ESDP/CSDP instruments - was demonstrated in Togo from 1993 to 2005, in the DRC with "Artemis" and EUFOR RD CONGO, in Darfur with EUFOR Chad-CAR and off the coast of Somalia with EUNAVFOR. Yet the need to highlight its strengths and play down its weaknesses leads it to promote the concepts of complementarity and ownership in the construction of the African Peace and Security Architecture through operations and civilian missions, in particular EUSEC and EUPOL in the DRC, EUTM "Somalia", EUAVSEC in Southern Sudan and Niger Sahel EUCAP and EUCAP Nestor for the training of national forces in the fight against Islamist terrorism and maritime piracy.What adjustments and improvements to European, pan-African and international law are required, with a view, in particular, to more innovative forms of funding and better coordination, as well as a pooling of African resources and the various forms of assistance from foreign contributors attracted by the resources and the economic opportunities of sub-Saharan Africa in the 21st century? This opens up a whole new and wide-ranging debate.
Keywords: African Research